(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article states that English as a Second Language (ESL) learning develops and reinforces four basic language competencies: speaking, listening, reading, and writing. These ESL competencies are linked to spoken and written communication and are organized into three subject-specific competencies. Teachers can help students develop skills in locating, evaluating, organizing, and retaining information from reading. Furthermore, the article provides information on continuous professional development and its role in future teachers’ success.